"Age XXL": Activities And Impact Of The Intergenerational And Inclusive Project In The School Community, Prisoners And The Elderly's Perception. Issue 4 (2nd October 2022) - Justo-Henriques, Susana I.
ABSTRACT: With the aging population, there is a need to develop intergenerational activities to promoting healthy aging. " Age XXL" was an intergenerational project in Portugal where older adults attending an institution providing social care and support services for this population exchanged correspondences with children, taught history and citizenship classes in schools and jails, and helped realize the dreams of other elderly people. The aim of this study was to identify the preliminary phases of the design of the intervention project, the activities developed, and the assessment of its social impact. Results show a better perception among the participants regarding their skills and contributions, enabling them to understand and recognize their importance in society.